Static and vibration analysis of sandwich cylindrical shell with functionally graded core and viscoelastic interface using DQM. (1st October 2017) - Aliyari Parand, A.; Alibeigloo, A.
Abstract: In the present paper, elasticity solution for static and free vibration analysis of sandwich cylindrical shell with functionally graded (FG) core and viscoelastic interface is carried out. Variation of Young's Module and material density of FGM core layer are assumed to obey power-law of radial coordinate with the Poisson's ratio holds to be constant. Imperfect interfaces are modeled according to the Kelvin-Voigt viscoelastic law. State space differential equations are derived using differential equations of motion as well as stress-displacement relations. For sandwich cylindrical shell with simply supported boundary conditions, these equations are solved analytically by using Fourier series expansion along the axial and circumferential direction. Whereas they are solved semi-analytically for the other cases of boundary conditions by using one dimensional differential quadrature method (DQM) along the axial coordinate. Time-dependent behavior is determined by solving first-order differential equation of sliding displacement at the viscoelastic interfaces. Numerical results are computed and compared with the reported results in literature to validate the present approach. In addition, effects of solid, elastic interfaces, different boundary conditions, time and mid radius to thickness ratio on the bending and vibration behavior of the sandwich shell are studied.